Speciation of uranium‐mandelic acid complexes using electrospray ionization mass spectrometry and density functional theory. (10th February 2017) - Kumar, Pranaw; Jaison, P.G.; Telmore, V.M.; Sadhu, Biswajit; Sundararajan, Mahesh
Abstract : Rationale: Mandelic acid is a complexing agent employed for the liquid chromatographic separation of actinides. However, the types of species and the structural details of the uranyl‐mandelate complexes are still unknown. Understanding the nature of these complex species would provide better insight into the mechanism of their separation in liquid chromatography. Methods: Formation of different species of the uranyl ion (UO2 ) with mandelic acid was studied using electrospray ionization mass spectrometry (ESI‐MS) with a quadrupole time‐of‐flight analyzer. The different species of uranyl nitrate with mandelic acid (MA) at ligand (L) to metal ratios in the range 1–10 were examined in both positive and negative ion modes. The stability of different species with the possible pathways of formation was scrutinized using density functional theory (DFT) calculations. Results: In negative ion mode, nitrate‐containing UO2 (MA)1, UO2 (MA)2 and UO2 (MA)3 species were found in good abundance. In positive ion mode, under‐coordinated uranyl‐mandelate species, and solvated (S) species of types UO2 (MA)1 (S), UO2 (MA)1 (S)2 and UO2 (MA)2 (S), were observed whereas nitrate‐containing species were absent. Interestingly, doubly and singly charged dimeric species were also identified in positive ion mode. The theoretically computed energetics of the various species are in close agreement with their experimentally observed intensities in ESI‐MS. Conclusions: The most intense peak observed in ESI‐MS, UO2 (MA)3, was found to be the energetically most favorable amongst different UO2 (MA)n type species. Metal‐ligand equilibria studied in the two modes yielded similar results. The combined experimental and quantum chemical investigations predict that T‐shape complexes may be formed even in the gas phase. Copyright © 2016 John Wiley & Sons, Ltd.